METHODS OF TEACHING ENGLISH TO CHILDREN - Abdullayeva Nigora Shavkatovna; Maxmudova Gulnavoz Ikromjon qizi (TADQIQOTLAR.UZ, 2023)
Abstract:This article analyzes the extensive work being done on the formation and strengthening of language learning skills in children and their results. Also, what kind of literature can be used to teach English to children. The results of many years of work will determine the future of their children.